Trends in the study of implicit alcohol related cognition - Ayelén Biscarra, María (2017)
According to the dual process model, the interaction between explicit (controlled) and implicit (automatic) cognitions would allow the understanding of irrational actions like addictive behaviors. This model has gained great popularity among addiction researchers, leading to an exponential growth in publications on implicit alcohol related cognition (IAC). Hence, the goal of this article is to identify trends in the study of IAC by means of a bibliometric and content analysis of the empirical studies published up to May, 2013. Throughout this paper, the studied topics of IAC were characterized, the most prolific countries, authors and journals were recognized, the most cited publications were detected and the most employed methods were identified.